The Effect Of LDR, ROA, PER, DER, NPL On Stock Prices In Banking Sub-Sector Companies In 2019-2021 - Ayu Putri Rizkia (Politeknik Ganesha Medan, 2023)
The purpose of this work is to analyze the impact of financial indicators on the stock prices of bank subsidiaries in 2019–2021. This study focuses on five ratios which are Loan to Deposit (LDR), Return on Assets (ROA). , price/earnings ratio (PER), debt/equity ratio (DER) and non-performing loans (NPL). The research method is panel regression analysis, which uses secondary information obtained from the financial statements of listed banking companies. The research sample consists of several banking companies of a certain period. The results of this study show that LDR, ROA, PER, DER and NPL significantly affect the stock prices of bank subsidiaries. LDR, ROA and PER have a positive effect on stock prices, while DER and NPL have a negative effect. This indicates that investors tend to pay attention to these financial ratios when evaluating a company and setting stock prices. This study helps to understand the factors affecting stock price of banking companies. The results of this study can be used as benchmarks for investors, corporate management and regulators in making investment decisions and policies related to banking.